Factors Associated with Medical Students’ Career Choices Regarding Internal Medicine in Uganda - Bongomin, Felix; Olum, Ronald; Kajjimu, Jonathan; Kanyike, Andrew Marvin; Atulinda, Linda; Ninsiima, Daphine; Kisaakye Wamala, Nicholas; Byakika-Kibwika, Pauline (Research Square, 2022)
There is an unmet need for internal medicine physicians in Uganda owing to the growing burden of diseases. This study aimed at evaluating the factors associated with career choices of undergraduate medical students regarding internal medicine in Uganda. Methods We conducted a cross-sectional study in the first 3 weeks of October 2021 via WhatsApp messenger. Medical students in the 3rd to 5th year of study who had completed internal medicine clinical rotations and pursuing a Bachelor of Medicine and Bachelor of Surgery (MBChB) degree at 7 Ugandan universities (4 public and 3 private) were enrolled. Multivariable logistic regression model was constructed to determine factors associated with a career choice in internal medicine. Results We enrolled 418 participants, median age 24 (interquartile range (IQR): 23 – 26) years, 67.7% were male, and 36.1% had a family member or relative who was a doctor. Most of the students (84.0%) were interested in research. The top three most preferred specialties were internal medicine (52.6%), surgery (51.2%), and obstetrics & gynaecology (51.0%). Overall, 186 (44.5%) participants reported plans to pursue a Master of Medicine degree in internal medicine. Interest in research was the only factor independently associated with 2.5-fold higher odds of pursuing a career in internal medicine (adjusted odds ratio: 2.5, 95% CI: 1.4 — 4.6, p=0.003). About 73% of the participants strongly agreed that internal medicine requires wide reading. Conclusions There is strong interest to pursue a career in internal medicine among Ugandan medical students. We recommend increase in training opportunities in Internal Medicine especially in view of the growing disease burden and increasing population growth.
Keywords: Internal medicine; Career choices